265 Blue Light Filtering Laptop and Tablet Screen Protectors Used After Sunset Improve Sleep. (3rd May 2021) - Rus, Holly; Danoff-Burg, Sharon; Weaver, Morgan; Rodriguez, Rodolfo; Raymann, Roy
Abstract: Introduction: Light exposure at night is associated with altered sleep behavior and impaired sleep satisfaction, in part due to suppressing the release of melatonin. According to a National Sleep Foundation poll, 90% of people report using electronic devices within an hour of bed at least a few times per week. This study aimed to examine how use of EyeJust, a blue light filtering screen protector applied to laptops and tablet devices, impacted sleep. Methods: A within subjects, pre-post intervention design was implemented. Adults (n=24) who self-reported regular blue light exposure after sunset and eye strain participated in a 6-week study (3 weeks of baseline followed by 3 weeks of product use). Intervention consisted of the use of blue light filtering screen protectors on iOS devices used after sunset. Sleep was measured objectively each night using SleepScore Max and by self-report. Participants also reported level of eye strain each night. Multilevel regression and paired t-tests were used to test for statistical significance. Results: Across participants (75% female; age 21-50, avg. 37), there were 850 nights of sleep measured. When measured pre-post, many aspects of perceived sleep improved when using the screen protectors: sleepiness at bedtime, falling asleep in the preferred amount of time, ability to sleep through the night, feeling rested in the morning, sleep quality, and satisfaction with sleep (ps<.05). When measured daily, improvement was seen in eye strain, perceived time to fall asleep, perceived awakenings, and time spent awake at night (ps<.05). Objective sleep improvement was found in a subgroup of younger adults (age 21-35). They spent more time in bed (p=.03) and slept longer (6 hours, 40 minutes on average during baseline vs. 6 hours, 50 minutes during intervention; p=.04). This subgroup also had more REM sleep as reflected by a 2% increase in MindScore (measure of REM sleep; p=.04) Conclusion: Using blue light filtering screen protectors helped improve sleep, measured by self-report and objectively, especially among younger adults. This intervention may help reduce the negative impact electronic devices have on sleep. Support (if any): EyeJust